HR Management in The Digital Era: Integrating Technology for Organizational Success - Aan Yulianto; Harries Madiistriyatno (Return : Study of Management, Economic and Bussines, 2023)
Human resource management is a series of processes and activities that involve recruiting, developing, evaluating and managing employees to achieve individual and organizational goals. Human resources are an important asset and act as the main driving factor in the implementation of all agency activities, so they must be managed well through Human Resources Management (HRM). In the digital era, Human Resource Management (HRM) faces significant challenges and opportunities. Challenges include rapid changes in technology, the need for new skills, data security, increasing reliance on automation, and increasingly fierce global competition. However, there are huge opportunities in data analytics, more efficient recruitment, data-driven decision making, more personalized employee development, improved work-life balance, flexible work policies and employee empowerment. With the right strategy, organizations can successfully integrate technology in HRM, increasing efficiency, productivity and employee satisfaction. It is important to continuously monitor technological developments and adapt to ongoing changes to remain relevant in an increasingly digital world of work. With a wise approach, HRM can utilize technology to achieve organizational goals and provide great benefits for all parties.